Research on fast response criterion of power grid distributed loads after HVDC block fault - Yuling Wang; Wannan Zhang; Haishun Sun; Yingmeng Xiang; Di Shi; Zhiwei Wang (IET Generation, Transmission & Distribution, 2020)
The system equivalent inertia of the power grid is gradually decreased with the increasing penetration of renewable energy resources, which leads to a higher risk of frequency fluctuation after a major fault. For the frequency emergency control in the scenario of a high‐voltage direct current (HVDC) line block fault, a novel criterion for enabling the fast response of user‐end distributed loads is proposed in this study based on voltage feature identification and frequency drop detection. The reactive power to voltage sensitivity coefficient is combined with the Hausdorff algorithm to increase the accuracy of the calculation. The proposed criterion can realise the HVDC block fault identification at the end of the distribution grid, so as to achieve fast decentralised decision‐making for distributed loads. This method may greatly reduce the need for high‐speed communication and take actions faster than the primary and secondary frequency controls of the traditional units. The criterion makes it possible for low voltage small load in the user‐end to be controlled precisely and selectively to fill the large power imbalanced caused by an HVDC block fault. The validity and superiority of the criterion are verified by simulation experiments using multiple test systems.